Arterial vascularization of the uterus and ovary in Gaddi sheep - Rajput, Rajesh; Bhardwaj, R L; Pathak, Virender (The Indian Journal of Animal Sciences, 2007)
Arterial vascularization pattern in the female reproductive tract of 20 Gaddi sheep was investigated. The uterus received arterial blood supply mainly from uterine artery which arose from the internal iliac artery, a branch of umbilical artery of the abdominal aorta. The uterine artery supplied to the horn, body and cervix of the uterus. The ovary was supplied by the ovarian artery arising directly from the abdominal aorta and reached the ovary by way of mesovarium. The uterine artery and the ovarian artery anastomosed with each other. Uterine artery was the main artery to the uterus.